Commercializing Sonic Seasoning in Multisensory Offline Experiential Events and Online Tasting Experiences - Spence, Charles; Wang, Qian Janice; Reinoso-Carvalho, Felipe; Keller, Steve (Frontiers in Psychology, 2021)
The term “sonic seasoning” refers to the deliberate pairing of sound/music with taste/flavour in order to enhance, or modify, the multisensory tasting experience. Although the recognition that people experience a multitude of crossmodal correspondences between stimuli in the auditory and chemical senses originally emerged from the psychophysics laboratory, the last decade has seen an explosion of interest in the use and application of sonic seasoning research findings, in a range of multisensory experiential events and online offerings. These marketing-led activations have included a variety of different approaches, from curating pre-composed music selections that have the appropriate sonic qualities (such as pitch or timbre), to the composition of bespoke music/soundscapes that match the specific taste/flavour of particular food or beverage products. Moreover, given that our experience of flavour often changes over time and frequently contains multiple distinct elements, there is also scope to more closely match the sonic seasoning to the temporal evolution of the various components (or notes) of the flavour experience. We review a number of case studies of the use of sonic seasoning, highlighting some of the challenges and opportunities associated with the various approaches, and consider the intriguing interplay between physical and digital (online) experiences. Taken together, the various examples reviewed here help to illustrate the growing commercial relevance of sonic seasoning research.